Redemption - Walden, Mark (Walden, Mark. Earthfall trilogy, 2018)
Aliens have given twelve-year-old Sam Illuminate powers and are sending him a message to retrieve his "birthright" from the ancient alien spacecraft the Primarch--a digitized Illuminate consciousness gone insane from thousands of years of isolation. The Primarch urges Sam to join the fight to destroy the Vorem, and just when Sam thinks he's found a new ally, he discovers that the Primarch has an agenda of its own.